EMOTIONAL INTELLIGENCE, MENTAL TOUGHNESS, SELF-CONFIDENCE AND COMPETITIVE ANXIETY IN PREDICTING ATHLETE PEAK PERFORMANCE - Nugraha, Dwi Yan (International Journal of Psychosocial Rehabilitation, 2020)
Many factors that affect peak performance (PP) in athletes, including emotional intelligence (EI), mental toughness (MT), self-confidence (SC). However, these factors cannot be maximized without mediation by competitive anxiety (CA). This study wanted to determine the effect of EI, MT, SC, on CA, and PP, and the influence of CA on PP. In addition, this study also wants to see the role of CA mediation in increasing PP in athletes. The subjects in this study were 195 athletes. Data were collected using the Emotional Intelligence Scale (Lane, et al., 2009), Mental Toughness Questionnaire 48 (Vaughan, et al., 2017), Trait Robustness of Sport-Confidence Inventory (Faghir, et al., 2013), Sport Anxiety Scale-2 (Smith, et al., 2006), and Peak Performance (Fakhrurri, 2018) using the characteristics of PP from Garfield and Bennett (1984). Hypothesis testing uses the SEM approach which found that EI, MT, SC, affected CA (.023, .002, .02 < .05). Furthermore EI, SC, CA also influence PP (.000, .000, .035 < .05). However, MT has no effect on PP (.069 > .05). The findings of this study help young athletes to achieve PP in every match to the maximum and encourage their success in achieving achievements and bring victory in every match.